Mobile Database Computing Performance Related Issues and Replication with Recommendations - Khubaib Ahmed; Muhammad Nadeem (JISR Management and Social Sciences & Economics, 2005)
Analyzing characteristics of wireless medium and mobile hosts, provide typical performance related issues considered for mobile database design considerations to improve mobile database computing. In this paper we investigate issues that need to be addressed in mobile database development suitable for mobile computing environment and then provide high-level mobile database model. We are considering GSN based mobile network provided with data services to mobile clients accessing database server via small mobile phones, where limited bandwidth, instability of wireless environment and limited resourced mobile phones require light weight mobile database, keeping frequently access objects at mobile phone to improve performance and provides high data availability for disconnected operations. We also propose scheme along with simulation study which identify most frequently accessed objects to ensure high data availability for small memory mobile phones.